Flow preferences of upstream migrating Atlantic salmon (Salmo salar) - Lindberg, Dan-Erik (2016)
On their way from the sea to their spawning grounds in rivers, Atlantic salmon are often delayed or hindered by dams or other obstructions. Building a fishway can save a population that would otherwise go extinct. But even when there is a fishway present, sometimes the fish will have difficulties finding the entrance or navigating through the fishway. Understanding fish preferences during their upstream migration can help us improve fishway design so we can help the fish move upstream. The main goal of my studies was to find hydrodynamic preferences of salmon. We were able to show a preference for high turbulence intensity (I ~ 0.7). We also found a preference for lower water velocity. In my last study, I found most salmon near the highest available water velocity, which in light of previous results was interpreted as the salmon seeking out the turbulent areas in the boundary layer of the high velocity jet in the center of the river. There were several indications that Atlantic salmon prefer to save energy, and that they are able to utilize turbulent structures to save energy during their active migration. However, much of the proof was circumstantial and requires further investigation. As a main source of error, the instruments used to measure hydrodynamics were not precise enough. More focus should be put on developing better instruments, for example the newly invented artificial lateral lines.